To Look or Not to Look? Yes to Nodal Ultrasound!. Issue 6 (11th October 2021) - Rauch, Gaiane M; Kuerer, Henry M; Jochelson, Maxine S
Abstract: Knowledge of axillary nodal status is highly important for correct staging and treatment planning in patients with breast cancer. Axillary US is a recognized highly specific and cost-effective tool for assessing nodal status and guiding appropriate treatment. Axillary US imaging with US-guided biopsy is routinely performed throughout the world. However, because of recent developments in the surgical management of the axilla in patients with newly diagnosed breast cancer (American College of Surgeons Oncology Group [ACOSOG] Z0011 trial) and in patients with breast cancer receiving neoadjuvant systemic therapy (ACOSOG Z1071, SENTinel NeoAdjuvant [SENTINA] and Sentinel Node biopsy aFter NeoAdjuvant Chemotherapy [SN FNAC] trials), some have questioned the utility of axillary US for nodal staging. Here, we review the evidence to date supporting the additional value of axillary US for patients with breast cancer. Nodal US in patients with newly diagnosed breast cancer is useful for staging; in a significant proportion of patients, nodal US identifies additional axillary level II or level III nodal disease, which allows for appropriate treatment of disease. Furthermore, ongoing clinical trials may show that axillary surgery can be omitted in patients with negative findings on axillary US. In patients with lymph node–positive disease undergoing neoadjuvant systemic therapy, nodal US can guide the approach to axillary surgery. A more personalized patient approach, taking into the account tumor biology, among other factors, may help to mitigate the controversy surrounding the role of axillary US in breast cancer patients.